The Pictures in Enhancing Students English Learning - Susanti Susanti (JUDIMAS, 2020)
Writing is one of the four language learning skills which must be well-educated by the language learners. And it is as the most difficult skill to be executed which comes across by the students of the Vocational School of SMKN 4 Pontianak. The writing obstacles such as they do not know what should be written, what topics to be described, limited vocabularies, incorrectly grammar, and the coherency. Educators are desired to lend a hand the students with their learning complication, especially their writing skill. The Picture-Cued Technique is the practice to be carried out to the workshop of Community Engagement at the Vocational School of SMKN 4, which located on Komodor Yos Soedarso Street, Pontianak, Kalimantan Barat. The aim of this community engagement workshop to familiarize and to assist the learners of the Vocational School of SMKN 4 Pontianak with the procedure of the Picture-Cued Technique to facilitate their writing hindrances. The students of the Vocational School of SMKN 4, eleventh grade, consisted of 32 students who become the participants in this community engagement study. The outcome of this community engagement is students are familiarized to the Picture-Cued Practice then assist them in overcoming writing hindrances in learning writing competence.